mRNA-1273 vaccination induces polyfunctional memory CD4 and CD8 T cell responses in patients with solid cancers undergoing immunotherapy or/and chemotherapy - Gangaev, Anastasia; van Sleen, Yannick; Brandhorst, Nicole; Hoefakker, Kelly; Prajapati, Bimal; Singh, Amrita; Boerma, Annemarie; van der Heiden, Marieke; Oosting, Sjoukje F.; van der Veldt, Astrid A. M.; Hiltermann, T. Jeroen N.; GeurtsvanKessel, Corine H.; et al. (Frontiers in Immunology, 2024)
Research has confirmed safety and comparable seroconversion rates after SARS-CoV-2 vaccination in patients with solid cancers. However, the impact of cancer treatment on vaccineinduced T cell responses remains poorly understood. In this study, we expand on previous findings within the VOICE trial, and evaluate the functional and phenotypic composition of mRNA-1273-induced T cell responses in patients with solid tumors undergoing immunotherapy, or/and chemotherapy, and individuals without cancer. ELISpot analysis of 386 participants showed a robust induction of spike-specific T cell responses 28 days after full vaccination irrespective of treatment with similar response rates ranging from 75% to 80%.Further in-depth characterization of identified spike-specific T cell responses using flow cytometry in a subset of 63 participants revealed a distinctive cytokine production pattern across all cohorts, with CD4 T cells producing IFNγ, TNF, and IL-2, while CD8 T cells produced IFNγ, TNF, and CCL4. Spike-specific CD4 T cells displayed cohort-specific variations characterized by a higher proportion of monofunctional cells producing TNF in individuals without cancer and patients treated with chemotherapy alone, whereas patients treated with immunotherapy alone or chemoimmunotherapy predominantly produced IFNγ.Nevertheless, polyfunctional spike-specific memory CD4 and CD8 T cell responses were comparable across cohorts. Interestingly, immunotherapy-treated patients exhibited expansion of spike-specific CD4 T cells with a terminally differentiated effector memory phenotype.Overall, these findings highlight that systemic treatment in patients with solid tumors does not compromise the quality of polyfunctional mRNA-1273-induced T cell responses, underscoring the importance of COVID-19 vaccination in patients with solid cancers undergoing systemic treatment.